2017
DOI: 10.1002/2211-5463.12254
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian‐enabled (MENA) protein enhances oncogenic potential and cancer stem cell‐like phenotype in hepatocellular carcinoma cells

Abstract: Mammalian‐enabled ( MENA ) protein is an actin‐regulatory protein that influences cell motility and adhesion. It is known to play a role in tumorigenicity of hepatocellular carcinoma ( HCC ) but the underlying molecular mechanism remains unknown. This study aimed to investigate the oncogenic potential of MENA and its capacity to regulate cancer stem cell ( CSC )‐like phenotypes in HCC cells. Real‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Researchers have demonstrated that NCAPG is associated with the growth of hepatoma cells, apoptosis, and epithelial mesenchymal transformation (EMT) [24]; NAP1L1 was found to be a nucleosome assembly protein in response to nucleosome remodelling through CSB protein and chromatin remodelling [25], promoting tumour progression as a chromatin regulatory factor in liver cancer [26]; PEA15, an essential prognostic marker for HCC, is involved in negative regulation of apoptosis signalling pathway mediated by death receptor, thereby inhibiting apoptosis of hepatoma cells. In addition, PEA15 also participates in transmembrane receptor protein tyrosine kinase signalling pathway, which mediates cell communication and promotes the migration of liver cancer cells, and the high level of ENAH expression promotes the occurrence and metastasis of liver cancer [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have demonstrated that NCAPG is associated with the growth of hepatoma cells, apoptosis, and epithelial mesenchymal transformation (EMT) [24]; NAP1L1 was found to be a nucleosome assembly protein in response to nucleosome remodelling through CSB protein and chromatin remodelling [25], promoting tumour progression as a chromatin regulatory factor in liver cancer [26]; PEA15, an essential prognostic marker for HCC, is involved in negative regulation of apoptosis signalling pathway mediated by death receptor, thereby inhibiting apoptosis of hepatoma cells. In addition, PEA15 also participates in transmembrane receptor protein tyrosine kinase signalling pathway, which mediates cell communication and promotes the migration of liver cancer cells, and the high level of ENAH expression promotes the occurrence and metastasis of liver cancer [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…We found that TUG1 target genes NCAPG, VGLL4, HMGN4, PIGC, MCM6, NAP1L1, PEA15, GLS, HMGB2, PEA15, and ENAH were positively correlated with tumour stages (p < 0.05), suggesting that these target genes not only play a role in the development of liver cancer but also participate in tumour progression. For example, MCM6, PEA15, RACGAP1, and ENAH have been reported to promote the metastasis of HCC [17,[20][21][22][23][24][25][26][27][28][29][30]. The diagnostic effect analysis shows that TUG1 and its target genes have higher diagnostic efficacy than the traditional marker AFP in clinics, so further clinical trials are needed.…”
Section: Discussionmentioning
confidence: 99%
“…26 On the other hand, HCC cells can also get stem cell properties through EMT and have the ability of self-renewal and differentiation eventually to form a new metastasis. 27,28 Now many kinds of methods for the treatment of HCC may even induce EMT process of HCC to metastasis faster while slowing tumor growth. So, EMT is one of the important aspects for the prevention and control of HCC, and the inhibition of EMT has important therapeutic value in the treatment of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Park et al (2016) recently reported synergistic interactions between CD44 and TGF-β1 in EMT induction and CSC properties through the AKT/GSK-3β/β-catenin pathway in HCC cells. Moreover, Hu et al (2017) found that overexpression of mammalianenabled protein in HCC cells facilitated stem cell markers, EMT markers, and tumorigenicity through the extracellular signalregulated kinase (ERK) and β-catenin signaling pathways. In addition, it was confirmed that Aurora Kinase A (AURKA), an oncogene involved in tumor development, can induce the EMT process and CSC properties through the PI3K/Akt pathway; silencing AURKA inhibits radiation-enhanced cell invasiveness of HCC (Chen et al, 2017).…”
Section: Lcsc Acquisition Of Malignant Function By Emtmentioning
confidence: 99%